2018
DOI: 10.5334/jcr.167
|View full text |Cite
|
Sign up to set email alerts
|

Non-Image Forming Effects of Light on Brainwaves, Autonomic Nervous Activity, Fatigue, and Performance

Abstract: Fatigue and sleepiness are one of the main causes of human errors and accidents in the workplace. The empirical evidence has approved that, in addition to stimulating the visual system, light elicits brain responses, which affect physiological and neurobehavioral human functions, known as the non-image forming (NIF) effects of light. As recent evidences have shown the positive effects of red or low correlated color temperature white light on alertness and performance, we investigated whether exposure to 2564 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Such high diversity in light sensitivity has also been experimentally observed with more than a 50-fold difference across individuals 43 . In addition to stimulating the visual system, light elicits responses related to physiological and neurobehavioral functions, known as the non-image forming (NIF) effects of the light 44 . Light sensitivity has a critical effect on NIF functions, such as the circadian entrainment, and shifts the timing of circadian rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Such high diversity in light sensitivity has also been experimentally observed with more than a 50-fold difference across individuals 43 . In addition to stimulating the visual system, light elicits responses related to physiological and neurobehavioral functions, known as the non-image forming (NIF) effects of the light 44 . Light sensitivity has a critical effect on NIF functions, such as the circadian entrainment, and shifts the timing of circadian rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobehavioral responses indicate the relationship between the nervous system and human behavior. They typically include psychological processes such as alertness ( Lockley et al, 2006 ; Cajochen, 2007 ), mood ( Xiao et al, 2021 ), cognitive performance ( Alkozei et al, 2017 ) as well as different physiological states like heart rate ( Cajochen et al, 2005 ; Askaripoor et al, 2018 ) and body temperature ( te Kulve et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stress-related cardiovascular responses, endocrine responses, and autonomic responses are controlled by the PVN, the target of this study [34,35,36]. Previous studies in humans have reported that different light sources or color temperatures may alter the autonomic activity, psychological state, and working performance [22,23,24,25,26]. For example, it has been indicated that sympathetic nerve activity is increased at high color temperatures in association with autonomic activities [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans have reported that different light sources or color temperatures may alter the autonomic activity, psychological state, and working performance [22,23,24,25,26]. For example, it has been indicated that sympathetic nerve activity is increased at high color temperatures in association with autonomic activities [22]. In addition, it has been reported that parasympathetic nerve activity is enhanced to a greater extent under OLED light than under fluorescent light [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation